Pengaruh Kualitas Produk, Kualitas Pelayanan, Kemudahan, Emosional, dan Harga terhadap Loyal-itas Konsumen di Fruktosa Juice Bar Kapanewon Depok Kabupaten Sleman - Salsabila Agatha; Indah Widowati; Budiarto Budiarto (Agrisociabus, 2022)
The research conducted at Fruktosa Juice Bar aims to (1) describe product quality, service quality, ease, emotional, price, consumer loyalty, and consumer satisfaction at Fruktosa Juice Bar (2) analyze the direct and indirect effect of product quality, service quality, ease, emotional, and price on consumer loyalty at Fruktosa Juice Bar. The method used in this study is a quantitative research method with a case study approach. The method of taking respondents used a nonprobability sampling method with an accidental sampling technique. This study consisted of seven variables with the number of respondents in this study being 70. The data sources used are primary data and secondary data. The tools used for data collection use questionnaires, interviews, and documentation. Data analysis techniques with descriptive analysis and path analysis. The results of this study are (1) Product quality, service quality, and consumer satisfaction have a very high effect at Fruktosa Juice Bar. Meanwhile, the variables of ease, emotional, price, and consumen loyalty have a high effect at Fruktosa Juice Bar (2) Product quality, service quality, ease, emotional, and price have a direct effect on consumer loyalty and indirectly effect on consumer loyalty through the consumer satisfaction variable at the Fruktosa Juice Bar.